2016
DOI: 10.22159/ajpcr.2016.v9i5.13177
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Hepatoprotective Activity of Cassia Auriculata Polymer Nanospheres Containing Silymarin

Abstract: Objective: Hepatoprotective activity of herbal drugs has an importance in the treatment of hepatic disorders, but pharmaceutically engineered products are not evolved properly to cure the liver disorders properly based on the demand and also route, target the appropriate site of action. Methods:In our present work, we have been developed a new formulation that possesses a unique nature and site specificity for targeting the disease state. Here, we examined hepatoprotective activity of Cassia auriculata polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Multiple studies have indicated that natural toothbrushes such as Miswak possesses numerous valuable properties from a medical standpoint, such as being antiseptic, astringent, abrasive, detergent, enzyme inhibiting, and fluoridative [ [55] , [56] , [57] , [58] , [59] ]. Natural toothbrushes from plants are preferred as they do not require toothpaste, are cheap to obtain, easy to maintain, and can even tackle bad breath [ 60 ]. Therefore, although there has been a shift to using modern brushing techniques in Traditional African societies, natural toothbrushes are still popular in many countries [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have indicated that natural toothbrushes such as Miswak possesses numerous valuable properties from a medical standpoint, such as being antiseptic, astringent, abrasive, detergent, enzyme inhibiting, and fluoridative [ [55] , [56] , [57] , [58] , [59] ]. Natural toothbrushes from plants are preferred as they do not require toothpaste, are cheap to obtain, easy to maintain, and can even tackle bad breath [ 60 ]. Therefore, although there has been a shift to using modern brushing techniques in Traditional African societies, natural toothbrushes are still popular in many countries [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Natural toothbrushes from plants are preferred as they do not require toothpaste, are cheap to obtain, easy to maintain, and can even tackle bad breath [ 60 ]. Therefore, although there has been a shift to using modern brushing techniques in Traditional African societies, natural toothbrushes are still popular in many countries [ 60 ]. Therefore, it would be beneficial to popularise the use of natural toothbrushes, as they are more beneficial for our oral hygiene.…”
Section: Resultsmentioning
confidence: 99%